Utilization of Fishery Waste from The Morotai People's Market as Natural Flavoring - Andrha S. Pahana; Sandra Hi. Muhammad; Meysi Riska Seng; Alkadri M. Kasim; Moch Nurcholis Hj Djafar; Rinto Muhammad Nur (TECHNO: JURNAL PENELITIAN, 2024)
Capture fisheries production in Morotai continues to increase from 2019-2021, with an average annual production of 17,102.3 tons. The increase in capture fisheries production is in line with the amount of fish waste produced. In Morotai, fish waste is produced from fisheries processing industries and fish sales places such as markets. This waste has not been utilized and is thrown into the environment. Even though these wastes still contain nutrients, especially protein, they can be used to make flavorings. The main flavoring ingredient is glutamate. This research aims to utilize fish waste from the market as raw material for making flavorings. This research used an experimental method by making four variations of flavorings. Before being processed into flavoring, fish waste will be treated by soaking it in a whiting solution, baking soda solution, or pineapple juice without soaking it. The powdered flavoring obtained was then analyzed for its hedonic organoleptic value using 30 panelists. Proximate tests were also conducted to determine the water, protein, fat, and ash content. The research results showed that, on average, the panelists liked the powdered flavoring from fish waste that had been soaked with lime, pineapple, and baking soda without soaking. The results of the proximate analysis showed that the flavoring water content ranged from 11.30—19.59%, the protein content ranged from 19.74—30.97%, the fat content ranged from 0.59—30.97, and the ash content ranged from 18.11—23.62%.